The histone demethylase KDM5C enhances the sensitivity of acute myeloid leukemia cells to lenalidomide by stabilizing cereblon - Lu Zou; Dan Cao; Qing Sun; Wenjun Yu; Bingzong Li; Guoqiang Xu; Liang Zhou (Cellular & Molecular Biology Letters)
Abstract Background The protein cereblon (CRBN) mediates the antileukemia effect of lenalidomide (Len). Len binds to CRBN, recruits IKZF1/IKZF3, and promotes their ubiquitination and degradation, through which Len exhibits its antileukemia and antimyeloma activity. Therefore, the protein level of CRBN might affect the antiproliferative effect of Len. In this study, we explored the interactome for CRBN using proximity labeling technique TurboID and quantitative proteomics, and then investigated the antileukemia effect of Len. Methods The primary acute myeloid leukemia (AML) cells and AML cell lines were used to explore the functions of histone demethylase KDM5C on the antileukemia effect of Len. The cell viability and CRBN protein levels were evaluated in these cell lines. In addition, the KDM5C inhibitors were used to determine the effects of KDM5C enzymatic activity on the viability of AML cell lines. Results We identified that histone demethylase KDM5C was a CRBN-interacting protein. Biochemical experiments found that the CRBN-interacting protein KDM5C could stabilize CRBN and enhance the antileukemia effect of Len in an enzyme activity-independent manner. Furthermore, our studies revealed that the small-molecule compound MLN4924 could increase CRBN by elevating KDM5C.The combination of MLN4924 and Len can further increase the sensitivity of primary AML cells and AML cell lines to Len. Conclusions This study provides a possible strategy for a combination treatment with MLN4924 and Len for leukemia.